New approximate method for the stochastic simulation of chemical systems: the representative reaction approach - Kadam, Shantanu; Vanka, Kumar (Journal of Computational Chemistry, 2012)
We have developed two new approximate methods for stochastically simulating chemical systems. The methods are based on the idea of representing all the reactions in the chemical system by a single reaction, i.e., by the representative reaction approach (RRA). Discussed in the article are the concepts underlying the new methods along with flowchart with all the steps required for their implementation. It is shown that the two RRA methods {with the reaction \$ 2A \textbackslashrightarrow B \$ as the representative reaction (RR)} perform creditably with regard to accuracy and computational efficiency, in comparison to the exact stochastic simulation algorithm (SSA) developed by Gillespie and are able to successfully reproduce at least the first two moments of the probability distribution of each species in the systems studied. As such, the RRA methods represent a promising new approach for stochastically simulating chemical systems. (C) 2011 Wiley Periodicals, Inc. J Comput Chem, 2012
Keywords: approximate algorithm; Stochastic simulations

Nature of the active site in ziegler-natta olefin polymerization catalysis systems - a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (European Journal of Inorganic Chemistry, 2014)
Pull quantum chemical calculations with density functional theory (DET) show that a principal role of donors in Ziegler-Nana (ZN) oh-din polymerization catalysts is to coordinate to the metal center at the active sites on the MgCl2 surface. Thereby, the behavior of the catalyst is modulated to favor insertion over termination and, thus, polymerization occurs. This is shown to be true for a range of different donors. The calculations indicate that active sites that feature anionic chloride ligands at the titanium center (the conventional model for the active site) would lead to lower-molecular-weight riolymers. If an -OC2H5 group were present instead of a chloride ligand, the active site would much more effectively produce long chain polymers. Therefore, the current work provides important new insights into the nature of the ZN polymerization process.
Keywords: Alkene polymerization; Density functional calculations; heterogeneous catalysis; Insertion; Polymers

New insights into small molecule activation by acyclic silylenes: a computational investigation - Kuriakose, Nishamol; Vanka, Kumar (Dalton Transactions, 2014)
Recently synthesized acyclic silylenes have the potential to rival transition metal complexes in performing single site small molecule activation, which is significant because of the need to find cheap and green alternatives to transition metal complexes for this important class of reactions. However, the current computational study, a full quantum chemical investigation with density functional theory, demonstrates that undesired side reactions would be competitive in these systems during small molecule activation. The current investigation, in addition to shedding light on this problem, also provides solutions on how the undesired side reactions during small molecule activation can be avoided.

Nickel-catalyzed tandem conversion of paraformaldehyde : methanol to hydrogen and formate/chemo- and stereoselective hydrogenation of alkynes under neutral conditions - Subaramanian, Murugan; Padhy, Subarna Sukanya; Gouda, Chandrakanth; Das, Tamal; Vanka, Kumar; Balaraman, Ekambaram (Catalysis Science and Technology, 2024)
The development of new catalytic protocols for clean and COx-free hydrogen generation from fundamental feedstocks is always interesting and challenging. Herein, we disclose nickel-catalyzed dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free and activator-free conditions. The dihydrogen generation from this redox combination under neutral, oxidative coupling conditions has been integrated with the hydrogen transfer reactions such as chemo- and stereoselective hydrogenation of alkynes in a tandem manner. This unprecedented strategy provides diverse highly stereoselective olefins with excellent tolerance of reducible functional groups such as ether, silyl ether, aldehyde, keto, ester, nitrile, halides including bromo and iodo groups, and heteroarenes. Additionally, we demonstrated catalytic stereo-interconversion of alkenes under benign conditions. The affordable gram-scale synthesis of some important pharmaceutical bioactive molecules has further enhanced their synthetic value. A tandem dihydrogen generation from a mixture of paraformaldehyde-methanol under base-free conditions followed by semihydrogenation of alkynes is reported.

NHC-based diazo compounds: pathways to N2 liberation or dimerization - Balayan, Kajal; Tiwari, Prabhakar; Sharma, Himanshu; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Journal of Organic Chemistry, 2026)
We previously reported the C-H bond cleavage of Me3SiCHN2 by 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene (5-SIPr) to form 1. In this article, we showed that electron-poor diamido carbene 5-tBuDAC also cleaves the C-H bond of Me3SiCHN2 to form 5, unlike its ring-expanded congener 6-DippDAC, which forms N-heterocyclic methylene hydrazine. The divergence of reactivity has been explained with the help of DFT studies. Further divergence occurs when 1 and 5 were reacted with HCl. While dimerization was observed with 5-SIPr based diazoalkane to give quinoidal tetrazine (2), N2 elimination occurs from 5-tBuDAC based diazoalkane to afford 7 and 8. This contrasting behavior highlights the subtle yet profound influence of the N-heterocyclic carbene (NHC) framework on the fate of the diazo units. DFT studies shed light about the mechanism for the formation of 2 as well as reveal that N2 elimination is thermodynamically favored over dimerization for 5.

(NHC-olefin)-nickel(0) nanoparticles: an efficient and selective catalyst for hydrogenation reactions at low temperature and pressure - Avello, Marta G.; Singh, Geetika; Truong-Phuoc, Lai; Vidal, Loic; Papaefthimiou, Vasiliki; Chesse, Matthieu; Gruber, Nathalie; Chetcuti, Michael J.; Vanka, Kumar; Ritleng, Vincent; Pham-Huu, Cuong; Michon, Christophe (Journal of Catalysis, 2026)
The reduction of a NHC-cinnamyl nickel(II) organometallic complex through the use of different MeMgBr or MeMgCl reagents led to two types of NHC-olefin-coordinated nickel nanoparticles. Both of these unsupported nickel-NHC based nanomaterials behaved under hydrogen pressure as effective and selective catalysts operating at low temperature (<= 80 degrees C), pressure (<= 20 bar) and loading (<= 6 mol%) for the reductions of broad scopes of alkenes, alkynes, imines and heterocycles, including a challenging tetra-substituted alkene. Among these two nickel-NHC nanocatalysts, the one generated with MeMgCl showed a significant high catalytic activity with high yields and could stand the comparison with Raney nickel and state-of-the-art nickel nanocatalysts. For example, by studying the hydrogenation of 1-phenylcyclohexene in ethanol at 60 degrees C under 10 bar of H2, 3 mol% of this catalyst achieved the reaction within a single hour on a 5 mmol/0.8 g substrate scale with a yield of 96 %, a turnover number (TON) of 32 and a turnover frequency (TOF) of 32. Characterizations confirmed the coordination of the NHC-olefin ligands to the nickel nanoparticles, the reduced state of the nickel and the (poly-) crystallinity of the nanoparticles.
Keywords: alkenes; Alkynes; heterocycles; Hydrogenation; imines; N -heterocyclic carbene ligand; nanocatalysis; Nickel